Inhibition of Mitochondrial Oxidative Damage Improves Reendothelialization Capacity of Endothelial Progenitor Cells via SIRT3 (Sirtuin 3)-Enhanced SOD2 (Superoxide Dismutase 2) Deacetylation in Hypertension. Issue 8 (August 2019) - He, Jiang; Liu, Xing; Su, Chen; Wu, Fang; Sun, Jiapan; Zhang, Jianning; Yang, Xulong; Zhang, Chanjuan; Zhou, Ziting; Zhang, Xiaoyu; Lin, Xiufang; Tao, Jun
Abstract : Objective: Dysfunction of endothelial progenitor cells (EPCs) leads to impaired endothelial repair capacity in patients with hypertension, but the mechanisms remain incompletely understood. Mitochondrial oxidative stress is involved in endothelial injury in hypertension. In this study, we aim to investigate the role of mitochondrial oxidative stress in the deficient endothelial reparative capacity of EPCs and identify enhanced SIRT3 (sirtuin 3)-mediated SOD2 (superoxide dismutase 2) deacetylation as a novel endothelial protective mechanism in hypertension. Approach and Results: Hypertension-EPCs displayed increased mitochondrial reactive oxygen species and mitochondrial damage, including loss of mitochondrial membrane potential, abnormal mitochondrial ultrastructure, and mtDNA oxidative injury, which was coincided with impaired in vitro function and in vivo reendothelialization capacity. The harmful effects of hypertension on mitochondrial function of EPCs were in vitro mimicked by angiotensin II coincubation. Scavenging of mitochondrial reactive oxygen species with mitoTEMPO attenuated mitochondrial oxidative damage and rescued reendothelialization capacity. Enzymatic activity and deacetylation level of SOD2 were significantly reduced in hypertension-EPCs, which was accompanied with decreased SIRT3 expression. Knockdown of SIRT3 in EPCs resulted in mitochondrial oxidative damage, hyperacetylation of SOD2, and suppression of reendothelialization capacity. SIRT3 physically interacted with SOD2 and eliminated excess mitochondrial reactive oxygen species, restored mitochondrial function through enhancing SOD2 activity by deacetylation of K68. Upregulation of SIRT3/SOD2 signaling improved reendothelialization capability of EPCs. Conclusions: The present study demonstrated for the first time that mitochondrial oxidative damage because of deficient SIRT3/SOD2 signaling contributes to the decline in reendothelialization capacity of EPCs in hypertension. Maintenance of mitochondrial redox homeostasis in EPCs may be a novel therapeutic target for endothelial injury. Abstract : Supplemental Digital Content is available in the text.